PREPOSISI RING DALAM BAHASA BALI (The Preposition Ring in Balinese Language) - Ida Ayu Putu Aridawati (Kandai, 2012)
Prepositions ring marking the six relationships of meaning. The emergence of those meanings caused by the relationship between the lingual unit one with another unit in a sentence. The presence of preposition ring in a sentence can beas a core element filler (mandatory) and the outer core filler element (is not mandatory). As the filler element of core (mandatory) if it is suggested by thefiller verb of its predicate, while the outer core filler element (is not mandatory) or an additional element if it is not implied by the predicate verb filler. In the sentence  construction,  additional  elements  have  the  freedom  of  position.  Inaddition, the prepositions ring in sentence construction are arbitrary or can be vanished and there is also the mandatory characteristic or cannot be vanished. Preposisi ring dalam bahasa Bali menandai enam hubungan makna. Munculnya  makna-makna itu  akibat  adanya  hubungan  antara  satuan  lingualyang satu dengan satuan lingual lain di dalam sebuah kalimat. Kehadiran preposisi ring dalam kalimat dapat sebagai pengisi unsur inti (bersifat wajib) dan sebagai pengisi unsur luar inti (bersifat tidak wajib). Sebagai pengisi unsurinti (bersifat wajib) jika diisyaratkan oleh verba pengisi predikatnya, sedangkan sebagai pengisi unsur luar inti (bersifat tidak wajib) atau unsur tambahan jikatidak diisyaratkan oleh verba pengisi predikatnya. Di dalam konstruksi kalimat, unsur tambahan memiliki kebebasan letak. Selain itu, preposisi ring dalam konstruksi kalimat ada yang bersifat manasuka atau dapat dilesapkan dan adapula yang bersifat wajib atau tidak dapat dilesapkan.